Code-Mixing on Lyrics of Batak Pop Songs Martina I Love You from Trio Romansa - Abdul Gapur; Muhammad Pujiono; Taulia Taulia (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
This paper discusses code-mixing that occurs in the lyrics of Batak pop songs entitled "Martina I love you" popularized by Trio Romansa. The aims to identify the form of code-mixing contained in the lyrics of the song 'Martina I love you' from Trio Romansa Trio. To analyze the form of code-mixing and the type of code-mixing in the song lyrics used code-mixing theory which refers to the opinion of Suwito (1983). The method used is descriptive qualitative, namely research that is collecting, processing data and analyzing data at the time the research was conducted. The conclusions obtained from this paper are a code–mixing of Indonesian and English into the Batak language in the song lyrics. The mixed code forms contained in the song lyrics consist of the insertion of words, phrases and clauses. The insertion of words in the form of words in Indonesian is one word, phrases in Indonesian are three phrases, and clauses in English are ten clauses. The type of code-mixing used in the song lyrics is in the form of outer code mixing and inner code mixing. The code-mixing that occurs is related to the context of song content, the limitations of suitable vocabulary in Batak language and prestige in language.